Demulsification of water-in- oil (W/O) emulsion by microwave heating technology - Nor Ilia Anisa, Aris (2011)
Traditional ways of breaking emulsion using heat and chemicals are disadvantageous from both economic and environmental perspectives. In this thesis, the potentials of microwave technology in demulsification of water-in-oil emulsion is investigated. The work began with some characterisation studies to provide understandings of fundamental issues such as formation, formulation and breaking of emulsions by both chemical and microwave approaches. The aim was to obtain optimised operating condition as well as fundamental understanding of water-in-oil stability, upon which further developments on demulsification processes could be developed. The stability studies were carried out by analysing operating conditions such as stirring time, types of surfactant used, temperature, phase inversion, water-oil-ratio (10-90%) and stirring intensity. In this study, also for microwave and chemical demulsification performance tests, three crude oils, namely crude oil A, B and C were utilised. These crude oils were obtained from Petronas Penapisan Melaka, Malaysia. Among of these oils, crude oil C was found to be the heaviest and best for stability and followed by crude oil A and B, respectively. Results also showed that microwave heating of emulsions is advantageous as it was faster and more uniform. A microwave-assisted chemical system was then developed in crude oil A and C, and then successfully applied on demulsification of water-in-oil emulsions. Its performance was compared with conventional demulsification methods such as hotplate, chemical demulsifiers and gravity separation. For microwave irradiation, it was found that the microwave power was proportional to the volume rate of heat generation, rate of temperature increases, wavelength and penetration depth, while the volume fraction is proportional to dielectric properties and inversely proportional to the penetration depth and wavelength. In optimisation part, crude oil A and C obtained 23 factorial designs with microwave power, microwave processing time and demulsifier concentration. The percentage of water separated from the model crude oil A was 45.10% at 710 watt in 2.40 minutes with 0.15 wt% demulsifier, while for crude oil C was 38.03% at 767 watt in 2.50 minutes with 0.14 wt% demulsifier, respectively. Crude oil B acquired 22 factorial design with microwave power and time processing; the percentage of water separated was 64.07% at 692 watt in 2.56 minutes. The results obtained in this study have exposed the capability of microwave technology in demulsification of water-in-oil emulsion. Further works are nevertheless required to provide deeper understanding the mechanisms involved to facilitate the development of an optimum system applicable to the industry.